The Association of Other Autoimmune Diseases in Patients With Thyroid Autoimmunity - Alessandro Antonelli (Frontiers Research Topics, 2018)
Autoimmune thyroid diseases (AITD) are T cell-mediated organ-specific autoimmune disorders resulting from an immune dysregulation leading to a thyroid immune attack (Antonelli and Benvenga). Graves' disease and Hashimoto's thyroiditis are the two main clinical presentations of AITD, and their clinical hallmarks are thyrotoxicosis and hypothyroidism, respectively. In many cases, AITD may be associated in the same patient with other organ-specific autoimmune attacks (such as in the case of type II autoimmune polyglandular syndrome, or type I diabetes, etc). Furthermore, AITD and thyroid function abnormalities have been frequently described in patients with systemic rheumatologic autoimmune diseases. Conversely, patients affected with the above mentioned autoimmune disorders are more frequently affected by AITD. In this Research Topic, constituted by nineteen papers, we review and discuss new evidence about the association of other autoimmune diseases in patients with AITD. Among other organ-specific autoimmune disorders, the associations of AITD with chronic autoimmune gastritis (Cellini et al.), vitiligo (Baldini E et al.), lichen (Guarneri et al.), psoriasis (Ruffilli et al.), myasthenia gravis (Lopomo and Berrih-Aknin) and glomerulopathies (Santoro et al.) have been treated. Also the associations of AITD, in systemic autoimmune diseases have been treated (as Sjögren's syndrome, Baldini C et al.; systemic sclerosis, Fallahi et al.; systemic lupus erythematosus, Ferrari et al.; Antiphospholipid syndrome, Versini; sarcoidosis, Fazzi et al.; the autoimmune/inflammatory syndrome induced by adjuvants, Watad et al.; rheumatoid arthritis, Bliddal et al.; Hepatitis C Virus and mixed cryoglobulinemia, Ferri et al.; and, psoriathic arthritis, Ruffilli et al.). Furthermore peculiar aspects associated with post partum thyroiditis have been reviewed too (Di Bari et al., Le Donne et al.). The exact pathogenetic mechanisms underlying the above reported associations are not completely known. It has been hypothesized that the influence of genetic (Coppedè), and environmental factors (Antonelli and Benvenga), could lead to the onset of autoimmune phenomena in different organs in the same subject, characterized by predominance of a Th1 immune pattern at the beginning, and in the active phase of these disorders. In conclusion, an association of other autoimmune diseases in patients with thyroid autoimmunity has been shown, and this Research Topic provides an extensive update of the literature, and suggests interesting points for new investigations.